The Impact of Open Disclosure Implementation Following Patient Safety Incidents on Patient Trust and The Potential Medical Disputes in Hospitals: A Systematic Literature Review - I Putu Oka Yudaswara Pande; Farida Yuliaty; Kosasih Kosasih (Jurnal Ners, 2026)
Patient safety incidents remain a major concern in hospital services because they may affect clinical outcomes and public trust. Open disclosure is increasingly recognized as an ethical and communication-based response after patient safety incidents, yet its implementation remains inconsistent across healthcare settings. This study aimed to examine the concept and implementation of open disclosure, its relationship with patient trust, and its role in reducing medical disputes, complaints, and patient conflicts. This systematic literature review was conducted using Scopus, PubMed, and Google Scholar. The target population was peer-reviewed studies on open disclosure in healthcare contexts. Studies were selected through systematic searching and PRISMA-based eligibility screening using the keywords “open disclosure” AND “patient safety”. From 563 identified documents, 14 studies published between 2021 and 2026 met the inclusion criteria. The independent variable was open disclosure, while the dependent variables were patient trust, complaints, conflict resolution, medical disputes, and patient responses. Data were measured through structured extraction based on PICO and eligibility criteria, then analyzed using narrative synthesis. Among the 14 included studies, 6 were qualitative, 4 cross-sectional, 2 mixed-method, 1 quasi-experimental, and 1 retrospective observational. Most studies were conducted in Australia (n=3), followed by Ireland and multi-country studies (n=2 each). Open disclosure supported patient trust through honest, timely, empathetic communication, apology, and patient or family involvement. Full disclosure increased forgiveness (P<0.010), while partial and full disclosure increased intention to return for treatment (P<0.050). Complaints increased by 4.2% (p<0.010), whereas medicolegal cases decreased (CAGR=4.8%; p<0.050), with 88.6% resolved without legal proceedings. Open disclosure is an important hospital response strategy for restoring patient trust and reducing escalation of medical disputes. Its effectiveness depends on structured implementation, non-punitive culture, and healthcare professionals’ communication competence.